2013
DOI: 10.1080/00981389.2013.834031
|View full text |Cite
|
Sign up to set email alerts
|

Woman to Woman: A Peer to Peer Support Program for Women With Gynecologic Cancer

Abstract: Gynecologic cancer has significant emotional and psychosocial implications for patients and their families. This article describes the origin and implementation of a peer to peer support program providing emotional support and information to women in treatment for gynecologic cancer and their families, in collaboration with medical and social work staff in a large, urban medical center. A formative evaluation of the program is included which suggests program participants view the program as a helpful source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…The current study about peer support among patients with lung cancer adds to this, by elaborating the perspective of the creation of hope in chatting to a former patient -a peer-who has recovered. These findings is also in line with previous findings in other cancer groups as seen by Legg et al (2011) and Moulton et al (2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study about peer support among patients with lung cancer adds to this, by elaborating the perspective of the creation of hope in chatting to a former patient -a peer-who has recovered. These findings is also in line with previous findings in other cancer groups as seen by Legg et al (2011) and Moulton et al (2013).…”
Section: Discussionsupporting
confidence: 93%
“…Peer support can help reduce the patient's sense of isolation and increase knowledge about the experience of being ill and, in doing so, increase the range of possible coping strategies. Hence, peer support provides a sense of hope (Legg, Occhipinti, Ferguson, Dunn, & Chambers, 2011;Moulton et al, 2013;Ussher, Kirsten, Butow, & Sandoval, 2006). If the heavier conversations, which can often be laden with emotions and feelings, are held with peers who can relate to one's story, patient contact with caregivers and relatives can be rendered more free and less demanding (Ussher et al, 2006).…”
mentioning
confidence: 99%
“…The sharing of experiences and solutions to common problems provided additional support (Moulton et al, 2013) and reduced the feelings of isolation (Thompson et al, 2014). This way the relational element of the interventions validated and legitimised the relatives' own feelings (Harding et al, 2004).…”
Section: Regardless Of Whether the Interventions Were For Patients Almentioning
confidence: 99%
“…This "emotional benefit" (Beaven, Campbell, Jones, Masselos, & Cameron, 2008) was expressed in various forms. Patients needed to deal with their emotional turmoil and get "feelings out of their systems" (Omylinska-Thurston & Cooper, 2013) in order to reduce their "emotional isolation" (Donnelly et al, 2000;Moulton et al, 2013;Nekolaichuk et al, 2013). This involved "reassuring themselves when scared… pinpoint feelings… and deal with them" (Omylinska-Thurston & Cooper, 2013).…”
Section: Emotional Relief and A Sense Of Well-beingmentioning
confidence: 99%
“…Study participants were typically well educated. One study of online social support found that most had a polytechnic or college degree (39%), and nearly one in four (24%) had a university degree (43), while a study of one-to-one peer support found that 51% had a college degree (29).…”
Section: Who Participates In Peer Support Programmes?mentioning
confidence: 99%